Marital Matching, Economies of Scale, and Intrahousehold Allocations - Cherchye, Laurens; De Rock, Bram; Surana, Khushboo; Vermeulen, Frederic (The Review of Economics and Statistics, 2020)
We propose a novel nonparametric method to empirically identify economies of scale in multiperson household consumption. We assume consumption technologies that define the public and private nature of expenditures through Barten scales. Our method (solely) exploits preference information revealed by a cross-section of household observations while accounting for fully unobserved preference heterogeneity. An application to data drawn from the US Panel Study of Income Dynamics shows that the method yields informative results on scale economies and intrahousehold allocation patterns. In addition, it allows us to define individual compensation schemes required to preserve the same consumption level in case of marriage dissolution or spousal death.